Ab interno gel implant in patients with primary open angle glaucoma and pseudoexfoliation glaucoma - Hengerer, Fritz; Auffarth, Gerd U.; Yildirim, Timur Mert; Conrad-Hengerer, Ina (BMC ophthalmology, 2018)
To compare efficacy and safety results of an ab interno gel implant in patients with pseudoexfoliation glaucoma (PXG) and primary open angle glaucoma (POAG).